Railway track component condition monitoring using optical fibre Bragg grating sensors - Buggy, Stephen J.; James, Stephen W.; Staines, Stephen; Carroll, R.; Kitson, P.; Farrington, D.; Drewett, L.; Jaiswal, J.; Tatam, Ralph P. (Cranfield University, 2016)
The use of optical fibre Bragg grating (FBG) strain sensors to monitor the condition of safety critical rail components is investigated. Fishplates, switchblades and stretcher bars on the Stagecoach Supertram tramway in Sheffield in the UK have been instrumented with arrays of FBG sensors. The dynamic strain signatures induced by the passage of a tram over the instrumented components have been analysed to identify features indicative of changes in the condition of the components.
Keywords: fibre Bragg grating sensors; railway components; condition monitoring